The Roles of Base Modifications in Kidney Cancer - Feng, Chunyue; Huang, Xiaoli; Li, Xuekun; Mao, Jianhua (Frontiers in Oncology, 2020)
Epigenetic modifications including histone modifications, DNA and RNA modifications involve in multiple biological processes and human diseases including cancers. Kidney cancer is usually with poor prognosis, and the molecular mechanisms and therapeutic methods are still under intensive study. Kidney cancer is one of the common type of tumors and accounts for about 2% of all cancers. It is critical to understand the roles of epigenetic modifications and underlying mechanisms in kidney cancer, which is important for its diagnosis and clinic therapy. Recently, the function of DNA and RNA modifications has been uncovered in kidney tumor. In the present review, we have summarized the recent findings about the roles of epigenetic modifications with a focus on DNA modification and RNA modification in the incidence, progression and metastasis of kidney cancer, especially the renal cell carcinomas (RCCs).